The Impact of Internship on Students' Individual and Professional Development: The Mediating Role of Skills - Maryam Sadat Ghoraishi Khorasgani (Shahid Chamran University of Ahvaz, 2022)
IntroductionThe aim of this study was to investigate the mediating role of individual and professional skills in the relationship between internship and individual and professional development of educational students.MethodTo achieve this goal, descriptive-correlation method was applied. The statistical population consisted of students of educational sciences of Al-Zahra University (200 students). 143 samples were selected through availability sampling method. The standard Novotorov (2001) questionnaire was utilized to collect data. The face and content validity of the questionnaire were confirmed by 3 experts in the field of educational management. Reliability was obtained through Cronbach's alpha coefficient for the internship (0.88), individual development (0.84), professional development (0.88), individual skills (0.91) and professional skills (0.93) variables, which indicates the high reliability of the research tool. Data analysis was performed through SPSS16, AMOS22 software and structural equation modeling test.ResultsThe results indicated that the relationship between the impact of internship and individual /professional development and individual/professional skills and also the relationship between individual/professional development and individual/professional skills were positive and significant (p≤0.05).DiscussionBased on the results, internships are directly involved in the four areas of individual and professional skills and individual and professional development. As students' individual skills increase, internships will also indirectly affect professional skills. Consequently, it leads to the development of students' careers. The results also showed that internship has led to the individual and professional development of students. In general, internships can enhance students' individual and professional development if they enhance their professional skills. Finally, based on the findings, it is suggested that more supervision of internships be exercised by internship instructors through establishing continuous communication with interns and schools. Annual evaluation of internship courses by universities can also be effective in identifying obstacles and problems in its implementation. It is also necessary to hold symposiums and meetings jointly with Ministry of Education in order to show the significance of internships for students of educational sciences.